PENGUJIAN PENETRASI PADA WEBSITE ELEARNING2.BINADARMA.AC.ID DENGAN METODE PTES (PENETRATION TESTING EXECUTION STANDARD) - Rahmat Novrianda Dasmen; Rasmila Rasmila; Tantri Langgeng Widodo; Kundari Kundari; Muhammad Tio Farizky (Universitas Nusa Cendana, 2023)
Bina Darma University is one of the best private campuses that provides a website-based online learning system. With the increasing distribution of information online in the era of the Covid-19 pandemic and the high enthusiasm of students in online learning, it is very important for Bina Darma University to pay attention to the security of the information system website used to protect user data. The goal to be achieved in this research is to implement penetration testing with the Black Box method and the PTES method on the elearning2.binadarma.ac.id website. The PTES method can be used as a standard guide for assessing web-based application security which consists of 5 stages, which consist of information gathering, threat modeling, vulnerability analysis, exploitation, and reporting. At the end of the research, it can be concluded that testing on elearning2binadarma.ac.id was identified as having a loophole in Cross Site Scripting (XSS) which is quite dangerous if it spreads further. The way to handle this gap can be done by checking website vulnerabilities regularly.